Efficacy, immunogenicity and safety of a recombinant tetravalent dengue vaccine (CYD-TDV) in children aged 2–17 years: systematic review and meta-analysis - Rosa, Bruno Rodrigues (BMJ Open, 2019)
BACKGROUND: Randomised controlled trials have evaluated the recombinant tetravalent dengue vaccine (CYD-TDV). However, individual results may have little power to identify differences among the populations studied. OBJECTIVE: To evaluate efficacy, immunogenicity and safety of CYD-TDV in the prevention of dengue in children aged 2–17 years. DESIGN: Systematic review and meta-analysis. DATA SOURCES: MEDLINE (from 1950 to 5 December 2018), EMBASE (from 1947 to 5 December 2018) and Cochrane (from 1993 to 5 December 2018). ELIGIBILITY CRITERIA OF STUDIES: Randomised trials comparing efficacy, immunogenicity and safety of CYD-TDV with placebo or other vaccines for preventing dengue cases in children aged 2–17 years. OUTCOME MEASURES: Efficacy, immunogenicity and safety of CYD-TDV. STUDY APPRAISAL AND METHODS: Calculations were made of relative risk (RR) and mean difference (MD) for dichotomous and continuous outcomes, respectively. All estimates were calculated considering a 95% CI estimate. A p<0.05 was considered statistically significant. RESULTS: Nine studies involving 34 248 participants were included. The overall efficacy of CYD-TDV was 60% (RR 0.40 (0.30 to 0.54)). Serotype-specific efficacy of the vaccine was 51% for dengue virus type-1 (DENV-1) (RR 0.49 (0.39 to 0.63)); 34% for DENV-2 (RR 0.66 (0.50 to 0.86)); 75% for DENV-3 (RR 0.25 (0.18 to 0.35)) and 77% for DENV-4 (RR 0.23 (0.15 to 0.34)). Overall immunogenicity (MD) of CYD-TDV was 225.13 (190.34 to 259.93). Serotype-specific immunogenicity was: DENV-1: 176.59 (123.36 to 229.83); DENV-2: 294.21 (181.98 to 406.45); DENV-3: 258.78 (146.72 to 370.84) and DENV-4: 189.35 (141.11 to 237.59). The most common adverse events were headache and pain at the injection site. LIMITATIONS: The main limitation of this study was unclear or incomplete data. CONCLUSIONS AND IMPLICATIONS OF KEY FINDINGS: CYD-TDV is considered safe and able to partially protect children and adolescents against four serotypes of DENV for a 1-year period. Despite this, research should prioritise improvements in vaccine efficacy, thus proving higher long-term protection against all virus serotypes. PROSPERO REGISTRATION NUMBER: CRD42016043628.